Phase equilibria among η-Fe2Al5 and its higher-ordered phases. Issue 1 (31st December 2021) - Hamada, Tetsuya; Higashi, Masaya; Niitsu, Kodai; Inui, Haruyuki
ABSTRACT: Phase equilibria among the η -Fe2 Al5 phase and its higher-ordered phases with the η framework structure were determined experimentally. The solubility range of the η phase at elevated temperature does not differ remarkably from that in previous studies, but this phase is found to undergo complicated phase transformations upon cooling. Four phases are present, namely η ', η ", η "' and η m, with higher-order atomic orderings in the c -axis chain sites of the orthorhombic crystal structure of the parent η phase. The η " and η "' phases form on the Al-poor and Al-rich sides, respectively, in equilibrium with the ζ -FeAl2 phase below ~415°C and θ -Fe4 Al13 phase below ~405°C. The η ' and η m phases become stable below 312°C and 343°C with the peritectoid reactions η ' → η m  +  η "' and η m → η  +  η ", respectively. The η phase is not stable below 331°C with the eutectoid reaction of η m  +  η "' → η . On the basis of these findings, we unraveled the phase equilibria among the η -Fe2 Al5 phase and its higher-ordered phases with the η framework structure. Graphical abstract: uf0001